Fungsi Representasi Ideologi Kekuasaan dalam Tuturan Mata Najwa Bertema Politik - Siti Shofi Ima; Dawud Dawud (Universitas Negeri Malang, 2021)
Abstract: This research is focused on studying the function of ideological representation in political theme utterances of